Protective Effects of Zofenopril on Testicular Torsion and Detorsion Injury in Rats - Altunoluk, Bülent; Söylemez, Haluk; Bakan, Vedat; Ciralik, Harun; Tolun, Fatma Inanc (Urology Journal, 2011)
Purpose: To investigate the protective effect of zofenopril on torsion detorsion-induced biochemical and histopathological changes in experimental testicular ischemia or reperfusion injury in rats. Materials and Methods: A total of 35 prepubertal male Wistar-Albino rats were divided into five groups, including 7 rats in each group: Group I (sham, S), sham operation; group II (torsion/detorsion-early orchiectomy, T/D-E), 2 hours ischemia and 4 hours reperfusion; group III (torsion/detorsion-late orchiectomy), T/D-L), 2 hours ischemia and 5 days reperfusion; group IV (zofenopril-early orchiectomy, Z-E), 2 hours ischemia, 4 hours reperfusion, and a single dose of zofenopril; and group V (zofenopril-late orchiectomy, Z-L), 2 hours ischemia, 5 days reperfusion, and 5 doses of zofenopril. We determined the tissue levels of malondialdehyde, nitric oxide, glutathione peroxidase, and superoxide dismutase enzyme activities. Histopathologically, mean seminiferous tubule diameter measurements were used. Results: Malondialdehyde (3.490 ± 0.89 versus 1.729 ± 0.25 in early period; 3.837 ± 1.694 versus 1.694 ± 0.47 in late period) and nitric oxide levels (3.507 ± 0.44 versus 2.853 ± 0.54 in early period; 4.010 ± 0.72 versus 2.446 ± 0.29 in late period) significantly reduced and glutathione peroxidase (0.012 ± 0.001 versus 0.017 ± 0.001 in early period; 0.013 ± 0.002 versus 0.018 ± 0.001 in late period) and superoxide dismutase enzyme activities (58.030 ± 5.97 versus 70.773 ± 3.85 in early period; 57.421 ± 7.81 versus 76.329 ± 4.09 in late period) significantly increased in the testis tissue in zofenopril pretreated groups compared to group T/D both in early and late period (P < .05). The mean seminiferous tubule diameter was significantly better in pretreated group (210.33 ± 17.32) than group T/D (185.02 ± 22.45) only in late period (P < .05), but not in early period (209.38 ± 30.40 versus 208.21 ± 13.57; P > .05). Conclusion: Treatment with zofenopril decreased damage in ipsilateral testis caused by ischemia/reperfusion, and clinical application of zofenopril might be a new approach for the treatment of testicular torsion in addition to conventional detorsion.